Bioenergetics and Life's Origins - Deamer, David (Cold Spring Harbor Laboratory Press, 2010)
Bioenergetics is central to our understanding of living systems, yet has attracted relatively little attention in origins of life research. This article focuses on energy resources available to drive primitive metabolism and the synthesis of polymers that could be incorporated into molecular systems having properties associated with the living state. The compartmented systems are referred to as protocells, each different from all the rest and representing a kind of natural experiment. The origin of life was marked when a rare few protocells happened to have the ability to capture energy from the environment to initiate catalyzed heterotrophic growth directed by heritable genetic information in the polymers. This article examines potential sources of energy available to protocells, and mechanisms by which the energy could be used to drive polymer synthesis.